Environmental-Economic Analysis of Portable Mixed-Mode Greenhouse Dryer for Fig Leaves - Wan Nurlaila Mat Desa; Surya Dailiati; Hernimawati Hernimawati; Mulianti Mulianti; Hasna Rifdah Khairunnisa; Faisal Mahfud; Haznan Abimanyu; Ahmad Fudholi (Green Engineering Society, 2023)
Energy and environomical analysis play important role in designing a solar thermal drying system as these analyses identify the high energy-consuming area, formulate energy-saving measures and evaluate the size of any potential savings. In this study, a greenhouse solar dryer with a double-pass multi-hollow collector for leaf drying was evaluated using environmental-economic analysis. Environmental analysis includes the determination of embodied energy, energy payback time (EPBT) period, as well as CO2 emissions per year, carbon mitigation and carbon credit. The embodied energy of a passive dryer is 606.86 kWh and EPBT of 16.68 years, while for an active dryer, the values are determined at 636.17 kWh and 10.39 years, respectively. CO2 emission for the passive dryer is 47.17 kg per year, net CO2 mitigation of 124.6 kg, and earned carbon credit of RM 2.58 – RM 12.38. The active dryer has CO2 emission of 47.14 kg, net CO2 mitigation of 594 kg, and earned carbon credit of RM 51.95 – RM 247.66. Economic analysis of this dryer shows that the energy cost associated with its operation ranges from RM 1.59 to RM 4.77, monthly.